Comparative fatty acid profiling of seed lines of hemp (Cannabis sativa L.) and inhibition of tyrosinase, α-glucosidase and acetylcholinesterase - Saleepochn, Tharinee; Tharamak, Sorachat; Charanja, Sitanan; Pimsawang, Lalita; Wisarutwanit, Tipanan; Chaisan, Tanapon; Songoen, Weerasak; Pluempanupat, Wanchai (Agriculture and Natural Resources, 2024)
Importance of the work: Hemp (Cannabis sativa L.) has gained renewed interest for its potential in food and medicinal products, though its seeds remain underutilized. This study is the first to evaluate the fatty acid composition of hemp seeds using FAME analysis. It also examines the tyrosinase, α-glucosidase and acetylcholinesterase inhibitory activity of extracts from different hemp lines. Objectives: To analyze the fatty acid composition and assess the levels of tyrosinase, α-glucosidase and acetylcholinesterase inhibitory activity of various hemp seed lines for potential industrial applications. Materials and Methods: The fatty acid composition was determined based on FAME analysis with gas chromatography-mass spectrometry that provided fast and accurate assessment. The levels of tyrosinase, acetylcholinesterase and α-glucosidase inhibitory activity were evaluated to determine the percentage of inhibition. Results: Over 50% of the fatty acids in the hemp seed extracts were saturated fatty acids, with palmitic acid being predominant. The distribution of polyunsaturated fatty acids, including omega-3 and omega-6, and of monounsaturated fatty acids varied across lines, though there were no significant differences between lines E and G. Tyrosinase inhibitory activity varied significantly, with hemp line A producing the highest mean inhibition (29.2 ± 4.0%), while the others were in the range 11.1–29.1%. There were no significant differences in acetylcholinesterase inhibition across lines, ranging from 26.7 ± 1.0% to 28.3 ± 0.8%. Notably, all hemp seed extracts had high α-glucosidase inhibition, ranging from 97.0 ± 1.3% to 101.9 ± 1.0%. Main finding: This was the first report that the fatty acid composition across different hemp seed lines was not significantly different, which aligned with the consistent levels of acetylcholinesterase inhibition observed. However, there were notable differences in the levels of tyrosinase inhibition among the lines. Notably, all the hemp seed extracts had highly potent levels of α-glucosidase inhibition.